2006
DOI: 10.1111/j.1540-8183.2006.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Rheolytic Thrombectomy in Early Versus Late Myocardial Infarction

Abstract: Rheolytic thrombectomy with the AngioJet catheter is more effective in terms of improvement in coronary blood flow as assessed by TFCs when used less than 12 hours after the onset of clinical symptoms suggestive of AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Moreover, Antoniucci et al 13 showed a lower cTFC in the thrombectomy group with smaller infarct size and no MACE at 1 month. Makaryus et al also described procedural success of 75% with AngioJet ® thrombus aspiration in 61 patients presented with AMI 15 . On the other side, a recent large randomized AMI trial on routine use of a protection device during rheolytic thrombectomy with AngioJet ® , 21,22 as with other large trials on routine use of distal protection devices, 23,24 failed to demonstrate any positive effect on myocardial reperfusion or clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, Antoniucci et al 13 showed a lower cTFC in the thrombectomy group with smaller infarct size and no MACE at 1 month. Makaryus et al also described procedural success of 75% with AngioJet ® thrombus aspiration in 61 patients presented with AMI 15 . On the other side, a recent large randomized AMI trial on routine use of a protection device during rheolytic thrombectomy with AngioJet ® , 21,22 as with other large trials on routine use of distal protection devices, 23,24 failed to demonstrate any positive effect on myocardial reperfusion or clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have already described favorable outcomes with the use of aspiration thrombectomy, both in angiographic and clinical terms. In preliminary reports of the European AngioJet Rapid Thrombectomy Study (Euro‐ARTS), device success was obtained in 80% of patients, in the absence of death, reinfarction, and need of revascularization during thehospital stay 15,19,20 . In the Vein Graft AngioJet Study I(VeGAS I), TIMI 3 flow was reached in 88% of patients, with encouraging clinical outcome at 30 days 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations